Growth status and menarcheal age among adolescent school girls in Wannune, Benue State, Nigeria - Goon Daniel T; Toriola Abel L; Uever Jonathan; Wuam Sarah; Toriola Olutoyin M (BMC Pediatrics, 2010)
Abstract Background Menarcheal age is a sensitive indicator of environmental conditions during childhood. The aim of study is to determine the age at menarche and growth status in adolescents in a rural area of Tarka, Wannune, Nigeria. Methods Data on 722 female students (aged 12-18 years) were collected in February 2009. Height and weight were measured. Body mass index (BMI; kg m-2) was used as an index of relative weight. Results Mean and median menarcheal age calculated by probit analysis were 13.02 (SD 3.0) (95% CI: 13.02-13.07), and age 13.00 (SD 2.8) (95% CI: 12.98-13.04), respectively. Girls who reach menarche are significantly heavier and taller with higher BMIs than those of their pre-menarcheal peers. Conclusion The age of menarche is probably still declining in Nigeria. Although BMI is an important factor in the onset of menstruation, some other unmeasured environmental variables may be implicated in this population.